KEPEMIMPINAN PEMBELAJARAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SDQT NURUL ISLAM KARAWANG PADA ERA NEW NORMAL - Tita Heliyani, - (2021)
This research aims to create an effective learning leadership model design to be implemented in the new normal era. In this study, researchers use qualitative research design, data retrieval techniques through in-depth interviews, observations and documentation studies. Research informants include principals, deputy principals of curriculum sections, grade 1 teachers, grade 2 teachers, grade 3 teachers, grade 4 teachers, grade 5 teachers and grade 6 teachers . The results showed that the principal's instructional leadership has a very important contribution in improving the quality of learning at SDQT Nurul Islam by creating a conducive learning climate, managing the curriculum appropriately and flexibly, providing IHT (in house training) by optimizing Microsoft powerpoint for distance learning for teachers and education personnel as an effort to improve the quality of learning so that learning activities become fun so as to influence the improvement of the spirit of learning and motivation of learning students which then has implications on improving the learning achievements of SDQT Nurul Islam students. In improving the quality of learning a learning leader must be able to motivate all school residents to jointly do their best in order to achieve the school's goals, the principal as a learning leader must have a high spirit as an agent of change that is able to manage challenges and obstacles into an opportunity.